1999
DOI: 10.1128/iai.67.4.1633-1639.1999
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide Enhances the Production of Vascular Endothelial Growth Factor by Human Pulp Cells in Culture

Abstract: We investigated whether vascular endothelial growth factor (VEGF) production by human pulp cells (HPC) is regulated by lipopolysaccharide (LPS) in relation to the pathogenesis of pulpitis. Although HPC incubated with medium alone only marginally expressed VEGF mRNA and produced a low level of VEGF as detected by enzyme-linked immunosorbent assay, the VEGF mRNA expression and VEGF production were markedly enhanced upon stimulation with LPS from Escherichia coli. Prevotella intermedia LPS, phorbol 12-myristate 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(10 citation statements)
references
References 35 publications
0
9
0
1
Order By: Relevance
“…Human dental pulp cells were prepared as described previously (Matsushita et al, 1999). The use of the cells followed a protocol that was reviewed and approved by the Ethical Committee at Kagoshima University Dental School.…”
Section: Human Pulp Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Human dental pulp cells were prepared as described previously (Matsushita et al, 1999). The use of the cells followed a protocol that was reviewed and approved by the Ethical Committee at Kagoshima University Dental School.…”
Section: Human Pulp Cellsmentioning
confidence: 99%
“…In addition, sufficient consistent information about the effects of VEGF in cell types other than endothelial cells has not yet been obtained. We recently demonstrated that VEGF is spontaneously produced by human pulp cells (HPC) and that the production of this factor is enhanced upon stimulation with lipopolysaccharide (LPS) (Matsushita et al, 1999). More recently, one study indicated that dentin matrix contained VEGF, and it was suggested that release of VEGF from the matrix after injury may also contribute to the overall reparative response of pulp tissue (Roberts-Clark and Smith, 1999 (Masood et al, 1997), were synthesized and purified by Takara Shuzo (Tokyo, Japan).…”
Section: Introductionmentioning
confidence: 99%
“…VEGF has been found to be strongly expressed in teeth developing irreversible pulpitis (Güven et al, 2007); these irreversible vascular changes can affect dentinogenesis and progress to necrosis. LPSsinduced VEGF expression has been demonstrated in human dental pulp fibroblasts (Matsushita et al, 1999) and odontoblast-like cells (Botero et al, 2003…”
Section: Introductionmentioning
confidence: 99%
“…An increase in vascular density and permeability may become deleterious and contribute to irreversible pulp pathology, since the dental pulp has limited ability to relieve internal pressures (Heyeraas and Berggreen, 1999). It is known that lipopolysaccharides (LPS) from Gram-negative bacteria induce VEGF expression in macrophages (Sakuta et al, 2001), and in a mixed population of pulp cells (Matsushita et al, 1999). However, we do not know if LTA from Gram-positive bacteria has a role in the regulation of angiogenesis.…”
Section: Introductionmentioning
confidence: 99%